PHENOMENON OF DEMIKHOV. In the Sklifosovsky Institute (1960–1986). Approaches to solving the problem of organ and tissue transplantation in the USSR and abroad (1967) - S. P. Glyantsev (Трансплантология (Москва), 2021)
Analysis of the materials of the 2nd All-Union conference on the problem of tissue incompatibility, conservation and transplantation of tissues and organs (Odessa, 1967) showed that Soviet and foreign scientists had similar approaches to solving the problem of organ and tissue transplantation. Soviet scientists spoke about overcoming tissue incompatibility by hybridization of plants and chimerization of animals, about the effect of drug sleep on transplant immunity, about neurohumoral immunological shifts and the role of the central and peripheral nervous systems in the engraftment of grafts, about the influence of external factors on immunity. They also discussed the characterization of the antigenic structure of grafts, the role of DNA in immunity, the genetic transformation of homomaterial, the use of pharmacological agents to suppress immunogenesis, the cryopreservation of auto- and homo-organs and tissues with perfusion of their vascular bed, and the study of immunogenesis at the molecular level. A year earlier, the Americans discussed immunological paralysis, the effect on the recipient's immunity of the donor's blood transfused to him and its components, and biochemical studies of immunity. At the same time, without any ethical doubts, American scientists conducted experiments, including clinical ones, with multiple passages of homosexual skin, with exchange transfusion of blood to newborns and subsequent transplantation of homosexual donors to them, with irradiation of recipients with powerful doses of X-rays. It is shown that most of the trends that had been developed by V.P. Demikhov, were approved by the 2nd All-Union Conference. But what he lacked was close and comprehensive integration with morphologists, physiologists, immunologists, biochemists, pharmacologists and, sadly, with clinical surgeons. Based on the research conducted, an unambiguous conclusion can be drawn: Soviet scientists should not have criticized V.P. Demikhov for his "misunderstanding" of immunology, and to help him in every possible way, directing his energy in the right direction.